2021
DOI: 10.1007/s40262-021-01005-1
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and Drug–Drug Interactions of Long-Acting Intramuscular Cabotegravir and Rilpivirine

Abstract: Combined antiretroviral treatments have significantly improved the morbidity and mortality related to HIV infection, thus transforming HIV infection into a chronic disease; however, the efficacy of antiretroviral treatments is highly dependent on the ability of infected individuals to adhere to life-long drug combination therapies. A major milestone in HIV treatment is the marketing of the long-acting intramuscular antiretroviral drugs cabotegravir and rilpivirine, allowing for infrequent drug administration, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
89
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 78 publications
(93 citation statements)
references
References 67 publications
2
89
1
1
Order By: Relevance
“…The pharmacokinetic characteristics of long-acting CAB and RPV were recently reviewed in detail [ 20 ▪ ]. Briefly, sex and BMI contribute to variable pharmacokinetics for both intramuscular CAB and RPV; however, these two factors do not account for most of the variability observed.…”
Section: Cabotegravir and Rilpivirine For The Treatment Of Hivmentioning
confidence: 99%
“…The pharmacokinetic characteristics of long-acting CAB and RPV were recently reviewed in detail [ 20 ▪ ]. Briefly, sex and BMI contribute to variable pharmacokinetics for both intramuscular CAB and RPV; however, these two factors do not account for most of the variability observed.…”
Section: Cabotegravir and Rilpivirine For The Treatment Of Hivmentioning
confidence: 99%
“…27 Studies have shown that concentrations are detectable for more than 12 months after the last dose at levels that are insufficient to maintain viral suppression. 27,28 In the case of treatment discontinuation or unplanned missed injections, viral exposure to subtherapeutic levels of CAB could lead to ART resistance. More research is needed to establish the impact of suboptimal adherence.…”
Section: Long-acting Injectable Treatment Optionmentioning
confidence: 99%
“… 10 , 22 , 36 This nanosuspension technology increases the apparent t ½ of cabotegravir and rilpivirine, from 41 and 45 h to approximately 8.5 and 20.5 weeks, respectively, with the LAI formulation, although with substantial interindividual variability. 38 This variability in dose–exposure–response relationships could be addressed by TDM. In patients exhibiting substantially lower or higher C min , a personalized dosing schedule, shortening or extending the dosing intervals, could be implemented with benefits in terms of efficacy or costs, respectively.…”
Section: Molecules With Suitable Characteristics For La-artmentioning
confidence: 99%